Systematic incident command training and organisational competence. Issue 2 (25th December 2020) - Lamb, Katherine; Farrow, Malcolm; Olymbios, Costa; Launder, David; Greatbatch, Ian
Abstract : Purpose: The study aims to determine if the application of a systematic command training system (Effective Command) could influence the organisational competency profile, through the identification, training and assessment of key behavioural markers. Design/methodology/approach: The Effective Command framework is aligned to UK National Fire Service role-maps and is routinely used in both development and assessment of Fire Officers worldwide. Data from 1, 261 formal assessments were analysed and descriptive statistics performed. Findings: Structured analysis of incident command assessment data should inform subsequent training cycles of individuals, organisations and procedures. Key behavioural markers were identified in Level 1 (L1) and Level 2 (L2) commanders which influence assessment outcomes. Reduced competence scores between L1 and L2 officers were recorded, providing a strong argument for a supported development process for L2 officers. Practical implications: Six key behavioural markers were identified in L1 commanders, all were associated with information comprehension and evaluation, which ultimately impacted the outcomes of formal assessments. This study provides empirical evidence that frequent incident or scenario exposure, coupled with metacognitive understanding of the decision rationale could reverse these weaknesses and turn them into individual strengths. This in-depth analysis of data generated in individuals who pass or fail these assessments should strengthen organisational learning. Originality/value: The use of a structured command training framework contributes significantly to operational assurance by providing a robust assessment and training methodology, which ensures that organisations can appoint, train and assess their incident commanders.